2001
DOI: 10.1023/a:1011945623464
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine plus epirubicin plus taxol (GET) in advanced breast cancer: a phase II study*

Abstract: The results of the present study indicate that the addition of G to E plus T as front line treatment for advanced breast cancer is well tolerated with an ORR of 92%. On the basis of the high activity and interesting progression free and overall survival rates, the GET combination deserves further evaluation in randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 23 publications
1
23
2
Order By: Relevance
“…These adverse events are dose-and schedule-related with stomatitis being more frequent and severe at higher doses, while shorter dosing intervals lead to an increased incidence and severity of skin manifestations. However, in the present study, mucositis, a relatively frequent adverse event of PCX plus anthracycline plus GEM combination (Sanchez-Rovira et al, 2000;Conte et al, 2001;Zielinski et al, 2005), as well as PPE, were mild and uncommon. Moreover, neurotoxicity or cardiac toxicity, which already have been reported to complicate the PCX plus epirubicin plus GEM regimen (Sanchez-Rovira et al, 2000;Zielinski et al, 2005), were not observed in the present study.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…These adverse events are dose-and schedule-related with stomatitis being more frequent and severe at higher doses, while shorter dosing intervals lead to an increased incidence and severity of skin manifestations. However, in the present study, mucositis, a relatively frequent adverse event of PCX plus anthracycline plus GEM combination (Sanchez-Rovira et al, 2000;Conte et al, 2001;Zielinski et al, 2005), as well as PPE, were mild and uncommon. Moreover, neurotoxicity or cardiac toxicity, which already have been reported to complicate the PCX plus epirubicin plus GEM regimen (Sanchez-Rovira et al, 2000;Zielinski et al, 2005), were not observed in the present study.…”
Section: Discussioncontrasting
confidence: 52%
“…Indeed, the PK studies of doxorubicin in regimens containing PCX have demonstrated that the schedule-dependent increase in C max and AUC and the reduction in doxorubicin clearance were associated with severe neutropaenia and mucositis (Holmes et al, 1996) as well as cardiac toxicity (Gianni et al, 1997). Furthermore, the addition of GEM to the PCX/anthracycline combination was associated with an increased incidence of severe neutropaenia ranging from 62 to 72% of patients (Sanchez-Rovira et al, 2000;Conte et al, 2001;Cappuzzo et al, 2004;Zielinski et al, 2005). In order to improve the toxicity profile of the combination of PCX with anthracyclines, PLD was substituted for doxorubicin or epirubicin and the regimen was administered on a biweekly basis; this phase I study indicated that the regimen was very well tolerated with treatment delay due to grade 2 and 3 neutropaenia to be the dose-limiting event .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group has shown that the combination of gemcitabine+epirubicin+paclitaxel (GET) is very active with an overall response rate of 92% and a complete response rate of 31%; 6 the administration of high-dose thiotepa followed by high-dose melphalan as consolidation of GET induces an improvement in quality of response in 44% of patients. 7 On the basis of the promising activity and acceptable toxicity observed in this study, we were interested in evaluating the possibility of achieving further cell killing by administering another high-dose drug before high-dose alkylators.…”
Section: Static Breast Cancermentioning
confidence: 99%